Legal Protection for Consumers in Online Buying and Selling Transactions (E-Commerce) Reviewed Based on Law Number 8 of 1999 Concerning Consumer Protection - Amalia Putri Permatahati (Proceedings Series on Social Sciences & Humanities, 2023)
Internet technology has a huge influence on the world economy. This rapid development of technology has brought many changes to the pattern of life of most Indonesians. The pattern of life occurs in almost all fields, such as social, cultural, trade, science, and other fields. In the field of trade, the internet has begun to be widely utilized as a medium for business activities. The most developed example of trading activities in cyberspace in relation to the use of the internet is electronic commerce. E-Commerce is divided into two segments, namely business to business e-commerce (trade between business actors) and business to consumer e-commerce (trade between business actors and consumers). From this problem, the formulation of the problem to be discussed is how the responsibility of business actors towards consumers in the event of a discrepancy in the goods sent and how consumer protection is reviewed based on Law Number 8 of 1999 concerning Consumer Protection. The purpose of this research is to find out and analyze the liability of business actors to consumers for goods that are not in accordance with orders based on Law Number 8 of 1999 concerning Consumer Protection and to find out the provisions for consumer protection in online buying and selling based on Law Number 8 of 1999 concerning Consumer Protection. This research uses normative juridical methods, namely legal research conducted by examining library and secondary materials. Normative legal research is conducted on laws and regulations relating to consumer protection. The result of this research is that consumers must be given special protection from various possibilities that will harm consumers and business actors who do not have good faith in conducting online buying and selling transactions.